5G车载移动卒中单元医疗相关法律问题浅析（A Brief Analysis of Medical-Related Legal Issues in 5G Mobile Stroke Units） - 吴喜，李洪岩，张新博，郭松韬，李智强，杨军，郭伟，郭秀海，张洪钿，徐如祥(WU Xi, LI Hongyan, ZHANG Xinbo, GUO Songtao, LI Zhiqiang, YANG Jun, GUO Wei, GUO Xiuhai, ZHANG Hongtian, XU Ruxiang) (Zhongguo cuzhong zazhi, 2025)
5G车载移动卒中单元已应用于临床诊疗，并取得了良好效果，但是其应用中涉及的相关法律法规较少被探讨。本文依据医事法律法规并结合医疗合规管理经验，对5G车载移动卒中单元的医疗法律问题进行分析，以期为相关医疗活动的依法合规开展提供参考。Abstract: The 5G mobile stroke units have been applied in clinical diagnosis and treatment, achieving good outcomes. However, there is a lack of discussion on the relevant laws and regulations involved in their application. Based on medical laws and regulations combined with experience in medical compliance management, this paper analyzes the legal issues of the 5G mobile stroke units in medical practice, aiming to provide references for the legal and compliant conduct of related medical activities.